Intrinsic self-prestress ECC material, surface layer structure prepared from intrinsic self-prestress ECC material and application of intrinsic self-prestress ECC material
By controlling volume expansion and deformation in ECC materials, the intrinsic self-prestressing state is achieved, and the cracking problem caused by volume deformation during service of ECC materials is solved, and the innovation of maintenance-free ultra-thin and seamless ECC surface layer structure is achieved, which improves the durability and service safety of the structure.
Patent Information
- Application Number
- CN202510386192.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-03-31
AI Technical Summary
During service, the constrained tensile cracks caused by volume deformation such as temperature and shrinkage affect the durability of its structural and service safety. The ECC with high expansion agents is fast condensed, which is not conducive to construction and application.
The intrinsic self-prestressed ECC material that defines the volume expansion component is used to control its volume deformation, and the early maximum free expansion deformation is between 1500με-10000με, and after the later service stability, the free volume deformation is higher than 55% of the early maximum free expansion deformation, thereby maintaining the intrinsic precompression stress of 0.1MPa-10MPa.
The ECC surface layer structure is achieved to maintain a seamless state during service, and can self-heal even if cracks appear, and the thickness is reduced by 40-60% relative to the concrete surface layer of the same compressive strength grade.
Smart Images

Figure CN119912226A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of infrastructure structure and materials, and in particular to an intrinsic self-prestressed ECC material and a surface layer structure and application thereof. Background Art
[0002] In order to overcome the brittle failure of concrete, Professor Victor Li of the University of Michigan invented ECC (Engineered Cementitious Composite), an engineering cement-based composite material. After being tensile, ECC achieves a tensile ductility of more than 30,000 με through multiple micro-cracks, and exhibits tensile hardening ability. Due to different translation and naming angles, ECC is also often called high ductility concrete HDC, strain hardening cement-based composite SHCC, bendable concrete, ultra-high toughness cement-based composite (UHTCC), etc.
[0003] ECC has been innovatively applied in the field of seamless ultra-thin structures. Due to the excellent mechanical properties of ECC, ECC can reduce the thickness of traditional concrete structures, thereby achieving the purpose of saving materials and costs, such as "Sun Renjuan, Bu Linglai, Guan Yanhua, et al. An ultra-thin pavement structure and implementation process based on ultra-high toughness cement-based composite materials [P]" ultra-thin ECC pavement bearing layer. In addition, using the ultra-high tensile deformation capacity of ECC, ECC has been applied to seamless bridge decks and pavement structures to improve driving comfort and the durability of road and bridge decks. However, the above-mentioned seamless road and bridge deck technology transfers the deformation of concrete such as temperature, shrinkage, and load to the ECC surface layer, inducing ECC multi-crack cracking. Although ECC has a large crack resistance and deformation capacity, the durability and safety of ECC after multi-crack cracking are still worrying. Therefore, the above-mentioned is just a seamless maintenance-free structure without construction joints, not a truly seamless structure.
[0004] During the service of ECC, the external constraints on its volume deformation such as temperature and shrinkage will generate tensile stress and constrained tensile cracks, which will affect the durability and service safety of ECC structure. In particular, the drying shrinkage of ECC can reach 1500-3000με, which is 3-6 times that of traditional concrete. In order to alleviate the above problems, technicians in this field have obtained low shrinkage, zero shrinkage, and even expansion deformation ECC through internal curing, external addition of shrinkage reducers, expansion agents, etc.
[0005] Here, it is necessary to clearly distinguish two different concepts, that is, "expansion deformation ECC" is not equivalent to "pre-stressed ECC". High expansion deformation ECC can be obtained by increasing the dosage of expansion agent. However, due to the low elastic modulus and large creep of ECC in the early stage, the compressive stress generated by the early expansion deformation after being constrained is limited; the elastic modulus of ECC in the later stage is high, the creep is small, and the shrinkage is large, which will produce higher tensile stress. Therefore, "Zhu H, Zhang D, Wang T, et al. Intrinsic self-stressing and low carbon Engineered Cementitious Composites (ECC) for improved sustainability[J]. Cement and Concrete Research, 2021, 149: 106580." pointed out that expansion deformation ECC may still undergo tensile cracking.
[0006] In addition, the ECC with a high content of expansion agent has a fast setting speed, which is not conducive to actual construction application, especially in high temperature and dry construction service environments. In order to ensure that the ECC maintains prestress during service, it is necessary to comprehensively consider the reasonable amount of expansion agent, sufficient expansion deformation, controllable late shrinkage, complex service environment, dynamic material properties, etc. The coupling effect of the above complex factors forms a technical bottleneck that restricts the intrinsic self-prestressed ECC. Summary of the invention
[0007] The present invention aims to invent maintenance-free ultra-thin seamless ECC surface structure through comprehensive innovation of materials, structures, construction and maintenance, and is committed to the development of sustainable high-quality infrastructure. Specifically, it involves the fields of pavement, bridge deck, airport runway, ultra-thin box culvert, concrete panel, pumped storage power station panel, anti-seepage panel, marine ultra-thin large buoyancy float, floor panel, channel lining, tunnel lining, and renovation and repair of old structures.
[0008] The technical scheme of the present invention is as follows: an intrinsic self-prestressed ECC material, which is composed of 50-150 parts of volume expansion components, 100-800 parts of cement, 400-1200 parts of supplementary cementitious materials, 400-800 parts of aggregates, 200-400 parts of water, 0-30 parts of water reducers, 0-50 parts of shrinkage reducers, 0-10 parts of thickeners, and 10-40 parts of fibers in mass fraction.
[0009] The mass fraction of the volume expansion component is 16%-32% of the total mass fraction of cement and the volume expansion component; the mass of the supplementary cementitious material is 0.8-3.6 times the total mass of cement and the volume expansion component.
[0010] The intrinsic self-prestressed ECC material is composed of 75-150 parts of volume expansion components, 100-800 parts of cement, 400-1200 parts of supplementary cementitious materials, 400-800 parts of aggregates, 200-400 parts of water, 0-30 parts of water reducers, 0-50 parts of shrinkage reducers, 0-10 parts of thickeners, and 10-40 parts of fibers by mass fraction.
[0011] The intrinsic self-prestressed ECC material is composed of 75-130 parts of volume expansion components, 100-800 parts of cement, 400-1200 parts of supplementary cementitious materials, 400-800 parts of aggregates, 200-400 parts of water, 0-30 parts of water reducers, 0-50 parts of shrinkage reducers, 0-10 parts of thickeners, and 10-40 parts of fibers by mass fraction.
[0012] The intrinsic self-prestressed ECC material is composed of 100-130 parts of volume expansion components, 100-800 parts of cement, 400-1200 parts of supplementary cementitious materials, 400-800 parts of aggregates, 200-400 parts of water, 0-30 parts of water reducers, 0-50 parts of shrinkage reducers, 0-10 parts of thickeners, and 10-40 parts of fibers by mass fraction.
[0013] The volume expansion component is an early volume expansion component or a combination of an early volume expansion component and a late volume expansion component.
[0014] The early volume expansion component is one or more of sulphoaluminate cement, aluminate cement and calcium oxide; the late volume expansion component is one or a combination of magnesium oxide and steel slag.
[0015] The supplementary cementitious material is one or more of fly ash, granulated blast furnace slag powder GGBFS, silica ash, volcanic ash, steel slag powder, and high-altitude land.
[0016] The aggregate is one or more of machine-made sand, river sand, sea sand, desert sand, steel slag powder, tailings slag, limestone powder and rubber powder.
[0017] The fiber is one or more of polypropylene PP fiber, polyethylene PE fiber, polyvinyl alcohol PVA fiber, steel fiber, basalt fiber, carbon fiber, glass fiber, and fly ash fiber.
[0018] A maintenance-free ultra-thin seamless ECC surface layer structure, composed of the intrinsic self-prestressed ECC material, the intrinsic self-prestressed ECC material has a direct tensile deformation capacity of more than 30,000 με, a straight tension crack width of less than 100 μm, and a permeability coefficient of less than 10 after the intrinsic self-prestressed ECC material undergoes a direct tensile deformation of no more than 20,000 με and is in contact with water for 14 days. -8 m / s; maintain 0.1MPa-10MPa intrinsic pre-compression stress under external constraints during service.
[0019] The maintenance-free ultra-thin seamless ECC surface layer structure maintains an intrinsic self-prestressed state throughout the service process and self-heals after cracks appear; the four-point bending flexural strength of the maintenance-free ultra-thin seamless ECC surface layer structure is 8MPa-30MPa, and the thickness of the maintenance-free ultra-thin seamless ECC surface layer structure is 0.5-30cm, which is 60% lower than the thickness of the concrete surface layer with the same compressive strength grade.
[0020] The preparation method of the maintenance-free ultra-thin seamless ECC surface layer structure is as follows:
[0021] The volume deformation of the intrinsic self-prestressed ECC material during temperature and humidity curing is controlled to obtain a maintenance-free ultra-thin seamless ECC surface layer structure; the intrinsic self-prestressed ECC material maintains the intrinsic pre-compressive stress during service; the intrinsic self-prestressed ECC material is a high-ductility material.
[0022] The control of the volume deformation of the intrinsic self-prestressed ECC material during the temperature and humidity curing process is specifically: controlling the intrinsic self-prestressed ECC material to reach a maximum free expansion deformation between 1500με-10000με within 5 days during the temperature and humidity curing process, so that the free volume deformation after the later service stability is higher than 55% of the early maximum free expansion deformation.
[0023] The method of warm and wet curing includes water spraying curing and surface covering with plastic film, wet cloth, straw mat, moisturizing material and surface chemical moisturizing agent.
[0024] The temperature and humidity maintenance time is 0.25-3 days; the time after later service stability is 720 days or more.
[0025] The temperature and humidity curing process lasts for 0.5-2 days.
[0026] The temperature of the temperature and humidity curing is 10-40°C, and the humidity is greater than 95%.
[0027] Through any one or combination of secondary wet curing, adding steel slag, adding magnesium oxide, adding stone powder, the free volume deformation after later service stabilization is made higher than 55% of the early maximum free expansion deformation.
[0028] The secondary wet curing begins when the maximum expansion deformation shrinks to 60-80% of the maximum free expansion deformation, and the wet curing time is 0.25-3 days.
[0029] The temperature of the intrinsic self-prestressed ECC material is controlled at 5-30°C during mixing and transportation.
[0030] The construction method of the maintenance-free ultra-thin seamless ECC surface layer structure is that within 120 minutes from the start of construction, according to "GB / T2419-2020 "Determination Method for Fluidity of Cement Mortar", the fluidity of the intrinsic self-prestressed ECC material is between 120mm and 220mm.
[0031] The construction process is divided into one-time forming to achieve the designed thickness or into multiple layers of construction to achieve the overall designed thickness.
[0032] The construction method is one or more of injection molding, mold casting molding, 3D printing molding, rolling molding, self-compacting molding, and smearing molding.
[0033] A maintenance-free ultra-thin seamless ECC surface structure is used in marine buoys, pavements, bridge decks, airport runways, ultra-thin box culverts, concrete panels, anti-seepage panels, pumped storage power station panels, floor panels, channel linings, tunnel linings, spray repair thin layers, and hand-applied repair layers.
[0034] Beneficial effects of the present invention: The present invention is based on an intrinsic self-prestressed ECC material with a limited volume expansion component, and controls its volume deformation, so that the maximum free expansion deformation achieved by its early temperature and humidity curing is between 1500με-10000με, and the free volume deformation at 720 days and above is higher than 55% of the early maximum free expansion deformation, so that the maintenance-free ultra-thin seamless ECC surface layer structure formed maintains an intrinsic prestress of 0.1MPa-10MPa, thereby ensuring that it can still meet the seamless requirements under the influence of various environmental factors during service, and even if cracks appear, they can achieve self-healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The evolution law of fluidity expansion diameter and time under different curing conditions of C100 scheme.
[0036] Figure 2 The evolution law of fluidity expansion diameter and time under different curing conditions of C130 scheme.
[0037] Figure 3 The evolution law of fluidity expansion diameter and time under different curing conditions of C150 scheme.
[0038] Figure 4 The evolution law of fluidity expansion diameter and time under different curing conditions of C160 scheme.
[0039] Figure 5 Schematic diagram of the early free volume deformation of C130 ECC at different curing temperatures.
[0040] Figure 6Schematic diagram of the free volume deformation of C130 ECC at different curing temperatures for 180 days.
[0041] Figure 7 Schematic diagram of the early free volume deformation of C0 ratio ECC at different curing temperatures.
[0042] Figure 8 Schematic diagram of the free volume deformation of C0 ECC at different curing temperatures for 720 days.
[0043] Fig. 9 Free volume deformation of C130 ECC within 3 days.
[0044] Fig.10 Free volume deformation of C130 ECC within 720 days.
[0045] Fig.11 is the permeability coefficient of the ECC specimen pre-stretched to 20000με during the self-healing process.
[0046] Fig.12 Schematic diagram comparing maintenance-free ultra-thin seamless ECC pavement and traditional cracked concrete pavement.
[0047] Fig.13 Temperature monitoring results for maintenance-free ultra-thin seamless ECC pavement.
[0048] Fig.14 Deformation monitoring results for maintenance-free ultra-thin seamless ECC pavement.
[0049] Fig.15 Force-displacement curves of the three-sided compression test of ECC and concrete pipe elements.
[0050] Fig.16 This is the ductile failure mode diagram of ECC pipe with multi-point cracking.
[0051] Fig.17 This is the brittle failure mode diagram of concrete pipe.
[0052] Fig.18 This is an example of the ECC ultra-thin high buoyancy box-type floating structure.
[0053] Fig.19 It is an ECC ultra-thin high buoyancy box-type float multi-layer composite structure.
[0054] Fig. 20 It is an ECC box with FRP reinforcement for ECC ultra-thin high buoyancy box-type floating body.
[0055] Fig.21 Schematic diagram of the expansion and contraction of C50 under different strategies.
[0056] Fig. 22Schematic diagram of the expansion and contraction of C190 air-cured comparative samples under different strategies for C75-magnesium oxide.
[0057] Fig.23 Schematic diagram of the expansion and contraction of C75-slag under different strategies. DETAILED DESCRIPTION
[0058] 1. ECC material ratio and preparation
[0059] Exemplary mixture proportions are listed in Table 1. The cement is Portland cement, and sulphoaluminate cement (CSA) is used as a volume expansion component. The amounts of CSA in the C0, C100, C130, and C160 proportions are 0, 100, 130, and 160 kg / m 3 The machine-made sand with an average particle size of 200 μm and the rubber powder with an average particle size of 275 μm were used as ECC aggregates.
[0060] Table 1 (Unit: kg / m 3 ).
[0061]
[0062] This example adopts the strategy of mixing PE fiber and PP fiber to achieve the configuration goals of low cost and high performance ECC. In this example, the dosage of PP fiber and PE fiber is 10kg / m 3 In order to utilize the dispersion of PE fiber and PP fiber, water reducer and thickener are used together to adjust the viscosity of the slurry between 4–10 Pa•s. Table 2 lists the performance parameters of PE fiber and PP fiber.
[0063] Table 2
[0064]
[0065] Preparation process of intrinsic self-prestressed ECC material (hereinafter referred to as ECC): According to the materials in Table 1, firstly, cement, CSA expansion agent, fly ash, sand, rubber powder, thickener and other dry components were stirred in a mixer at 94 rpm for 5 minutes; then water and water reducer were added and stirred for 5 minutes; finally, PP fiber and PE fiber were added and stirred for 5 minutes at 174 rpm. The time of adding water was defined as time 0, which represented the starting point of recording the fluidity and volume deformation test.
[0066] During the stirring process, the stirring temperature needs to be strictly controlled at 5-30°C. The prepared ECC is cured under the environmental conditions shown in Table 3.
[0067] Table 3
[0068]
[0069] 2. Fluidity test and construction opening time evaluation
[0070] This example measures the fluidity of ECC according to GB / T2419-2020 "Method for determination of fluidity of cement mortar", and the results are as follows Figure 1 shown.
[0071] From the perspective of volume control, high CSA dosage can effectively reduce shrinkage and increase expansion deformation; however, too high CSA has a greater impact on fluidity loss, especially in high temperature environments such as summer. Figure 1-Figure 4 It shows that regardless of the CSA dosage and curing temperature, the fluidity loss of ECC shows a bilinear change law over time. In the first stage, the fluidity decreases slowly; after the critical turning point, the fluidity loss accelerates.
[0072] The amount of CSA added has little effect on the initial fluidity of ECC. In this example, the initial expansion diameters of C100, C130, C150 and C160 are all around 175 mm.
[0073] Increasing the CSA dosage and temperature accelerates the hardening of ECC and increases the fluidity loss rate. When the curing temperature is lower than 40°C, the fluidity loss over time is less affected by temperature; when the curing temperature is increased to 60°C, the fluidity of ECC decreases significantly over time. According to existing experience, when the flow expansion diameter of ECC is lower than 120mm, ECC will face challenges in construction and vibration compaction. Therefore, this example uses a flow expansion diameter higher than 120mm as the criterion for determining the construction window period.
[0074] Under 20-A curing conditions, C100, C130 and C150 can still maintain good constructability at 160 minutes, but the flow expansion diameter of C160 is already less than 120 mm at 130 minutes. Under 40-O curing conditions, the constructability window of C100 is higher than 160 minutes, the constructability window of C140 is about 140 minutes, and the constructability window of C150 is about 120 minutes. Due to the limitation of constructability, the upper limit of the volume expansion component in the intrinsic prestressed ECC material is determined to be 150 parts; in comparison, the constructability window of C160 is 110 minutes. It is worth noting that under the 60-O curing environment, the constructability window of C160 is significantly shortened to less than 80 minutes.
[0075] In view of the construction needs in the hot summer season, the temperature of ECC materials needs to be controlled during the construction period, such as cold water mixing or nighttime construction. At the same time, the amount of CSA should also be strictly controlled; high CSA content accelerates the loss of ECC fluidity on the one hand, and increases the hydration heat release on the other.
[0076] On the contrary, for the self-stress ECC demand, the higher the CSA content, the better. In the process of material research and development and application, it is necessary to comprehensively consider the construction window and self-stress demand to select the appropriate CSA content. In this example, C130 is selected as the ratio for subsequent volume deformation, mechanical testing, and pavement demonstration application.
[0077] 3. Free Volume Deformation Determination
[0078] This example tests the shrinkage deformation of 25mm*25mm*300mm ECC samples according to ASTM C490 / C490M–17. The earliest allowable demolding time is selected as the starting point of the volume deformation test. Table 4 records the maximum expansion deformation of ECC with different proportions under different curing environments and the volume deformation ratio after stabilization.
[0079] C50-2 days means 2 days of temperature and humidity curing for C50 in Table 1; C50-5 days means 5 days of temperature and humidity curing for C50 in Table 1; C50-stone powder-5 days means 5 days of temperature and humidity curing for C50-stone powder in Table 1; C75-3 days means 3 days of temperature and humidity curing for C75 in Table 1; C75-magnesium oxide and C75-steel slag are both the components shown in Table 1, and temperature and humidity curing is carried out for 3 days; C75-magnesium oxide-secondary curing and C75-steel slag-secondary curing are the component ratios in Table 1, and after the maximum volume deformation is reduced to 80%, secondary wet curing is carried out for 2 days; C100-24 hours means 24 hours of temperature and humidity curing for C100 in Table 1; C190-20-A means C190 in Table 1 is cured in air at 20°C.
[0080] Table 4
[0081]
[0082] The curing temperature has a great influence on the early expansion and late shrinkage of ECC. Figure 5 As shown in the figure, for the three curing conditions of 20-A, 40-O and 60-O, no temperature and humidity curing scheme was applied in the early stage, and C130 showed the pattern of first expansion and then contraction, and finally contraction. Under high temperature curing, the time of maximum expansion occurred earlier. For example, the maximum expansion of C130 under 60-O occurred 5 hours after the measurement, 40-O occurred 10 hours, and the maximum expansion of 20-A even occurred on the second day after the test. Under the 20-A environment, the highest expansion value of C130 was 551με, slightly higher than 40-O (520με) and 60-O (429με).
[0083] Figure 6The results show that the magnitude and development of the late shrinkage of 40-O and 20-A are basically the same, and the 180-day shrinkage of both is about 900με. The 180-day shrinkage value of 60-O is 1625με, which is 1.8 times that of 20-A and 40-O, and it still shows a trend of continued shrinkage.
[0084] Figure 7-Figure 8 The C0 mix did not have obvious expansion in the early stage, which was completely different from the volume deformation law of C130. High temperature curing accelerated the early shrinkage, but reduced the final shrinkage magnitude. Figure 7-Figure 8 As shown, the shrinkage value of C0 under 20-A curing conditions after 180 days is 1550με; in contrast, the shrinkage value under 40-O and 60-O curing conditions is only 900με.
[0085] Although the CSA content of C130 is as high as 130kg / m 3 , the shrinkage value of C130 at 180d is still as high as 900-1625με, which greatly increases the risk of cracking of ECC during service. If the content of CSA is further increased, it will be difficult to have sufficient construction time, especially in high temperature environments such as summer.
[0086] Fig. 9 The early temperature and humidity curing conditions required in this patent application are demonstrated, with a temperature and humidity curing humidity greater than 95% and a temperature of 10-40°C. The free volume deformation law of C130ECC under initial temperature and humidity curing of 6 / 12 / 18 hours. The maximum expansion deformation of ECC occurs within the initial 1-3 days, followed by volume shrinkage. Prolonging the early temperature and humidity curing time increases the magnitude of the maximum expansion deformation. In this example, the early maximum expansion deformations of 6 / 12 / 18 hours of temperature and humidity curing at 20°C are 3560με, 3800με and 4770με, respectively. At 1.5 days, the early maximum expansion deformation is 6125με; at 3 days, the early maximum expansion deformation is 7800με.
[0087] The temperature and humidity curing temperature also has a certain influence on the early maximum expansion deformation. 20℃ is the optimal temperature and humidity curing temperature. When the temperature and humidity curing temperature reaches 40 degrees Celsius, although the material still meets the volume deformation requirements, under the same conditions, the early maximum expansion deformation is less than the early maximum expansion deformation at 20℃.
[0088] After early temperature and humidity curing, C130 can maintain an expanded state for 180 days. The 180-day expansion deformations of temperature and humidity curing for 6 / 12 / 18 hours are 1803με, 2472με and 3251με respectively. The present invention unexpectedly found that different early curing strategies have little effect on the magnitude of volume shrinkage in the later stage. In this example, the volume deformation change is about 1333-1757με.
[0089] The total volume deformation of ECC is mostly distributed between 750-5000με, and it is necessary to ensure that the early maximum expansion is twice as high as the later shrinkage to ensure that the intrinsic self-prestressing effect is maintained under the external constraint service of ECC.
[0090] Furthermore, the mass fraction of the volume expansion component is controlled to be 16%-32% of the total mass fraction of cement and the volume expansion component, so that the maximum free expansion deformation peak is higher while meeting the construction window requirements.
[0091] Furthermore, when the mass fraction of the volume expansion component is 20% of the total mass fraction of cement and the volume expansion component, the best match between the maximum free expansion deformation peak and the construction window requirement is achieved.
[0092] Therefore, this patent application proposes a strategy of combining construction and maintenance, using a method that combines low-dosage CSA and a reasonable temperature and humidity maintenance strategy to break through the bottleneck of the incoordination between self-stress and the construction window period, and innovatively achieves the dual needs of intrinsic self-prestressing and construction window, so that the maximum free expansion deformation of the intrinsic self-prestressed ECC material during the temperature and humidity maintenance process is between 1500με-10000με, so that the free volume deformation in the later service is maintained at 55% higher than the maximum free expansion deformation in the early stage. The specific implications are as follows: sufficient temperature and humidity maintenance in the early stage can increase the maximum expansion deformation; secondly, high-temperature service should be avoided to avoid aggravating the volume shrinkage in the later stage; finally, if high-temperature construction is unavoidable, the temperature of the ECC material should be controlled below 40°C by adding ice, and preferably below 30°C.
[0093] When controlling the change in free volume deformation of intrinsic self-prestressed ECC materials in later service, the preferred solutions are secondary wet curing, adding steel slag, magnesium oxide or adding stone powder.
[0094] by Figure 22-Figure 23 For example, its volume expansion component is divided into an early expansion component and a late expansion component. In this embodiment, the early expansion component is CSA, and the late expansion component is steel slag or magnesium oxide. Since the early expansion deformation effect of steel slag / magnesium oxide is limited, its early maximum free expansion deformation is similar to that of C75. In its later service stage, the late expansion component begins to play an expansion deformation role, causing its volume deformation to increase secondary, and then slowly decreases to meet the volume deformation requirements.
[0095] Taking C75 as an example, after its initial warm and wet curing, it reached the highest free expansion deformation peak, after which its free volume deformation began to gradually decrease. About 10 days after its casting (the expansion was reduced to about 80%), it was wet-cured again, causing its free volume deformation to expand again. After experiencing the second peak, the free volume deformation deformed again, making the free volume deformation in the later service period higher than 55% of the highest free expansion deformation in the early period.
[0096] according to Fig.14 The actual monitoring results also confirm the effectiveness of secondary curing. Due to the fact that some volume expansion components did not fully play their role after the initial temperature and humidity curing, when it rained again, some volume expansion components played their role again, increasing the volume expansion deformation again. Based on this finding, the technical solution proposes a secondary wet curing solution, especially starting from the time when the maximum expansion deformation shrinks to 60-80%, which has the best effect of controlling the shrinkage of volume deformation.
[0097] Based on C75, stone powder is added to the intrinsic self-prestressed ECC material to ensure that the materials are fully mixed. Stone powder has a dual role. First, it can prevent the decomposition of ettringite and ensure the stability of the early expansion of ECC; second, it can reduce the shrinkage magnitude of ECC in the later stage. Combined with the strategy of early temperature and humidity curing for 5 days, the required self-stress purpose can still be achieved when the volume expansion component is a low dosage of 50 parts.
[0098] The increase in the proportion of the volume expansion component makes the maximum expansion deformation larger, but the volume deformation after stabilization needs to be controlled to be greater than 55% of the maximum expansion deformation. Fig. 22 For example, C190 in 3 Even if the temperature and humidity curing method is not used, its early maximum expansion increases to 3005με. However, since the final expansion deformation at 720 days is only 43% of the early maximum expansion, it does not meet the design requirements of self-stress.
[0099] 4. Mechanical properties test
[0100] Table 5 lists the mechanical properties of ECC cured for 28 days under different conditions. Temperature and humidity curing improves the compressive, bending and direct tensile strength of ECC; the strength of 20-A and 40-O is equivalent; the high temperature of 60℃ (60-O) reduces the strength and deformation capacity of ECC to a certain extent.
[0101] The compressive strength of the C130 ECC in this example is 40.2-44.5MPa, which is equivalent to the C40 strength grade of conventional concrete. Depending on the curing conditions, the four-point bending strength of ECC is 8.5-11.6MPa, and the direct tensile strength is 4.7-5.4MPa, both of which are more than twice that of conventional C40 concrete. The direct tensile strain capacity of ECC is 6.5%-8.4% (65,000-84,000 με), which is 600 times higher than the direct tensile strain capacity of concrete. The average crack width is less than 100μm at tensile failure. Thanks to the above high performance, the thickness of the maintenance-free ultra-thin seamless ECC surface structure can be reduced by 40-60% or even higher than that of concrete with the same compressive strength grade.
[0102] Table 5
[0103]
[0104] 5. Self-healing ability
[0105] The mix C130 in this example was subjected to direct tensile testing after 28 days of 20-A curing. After being stretched to 20,000 με, the dog-bone specimen was unloaded and then immersed in water for 14 days. In one example, the average crack width before healing was 30 μm, and the crack was completely self-healed after 14 days of water immersion. Fig.11 It shows that the permeability coefficient of ECC cracked at 20,000 με can still be maintained at 10 - 7 m / s; the permeability coefficient of the specimen gradually decreased after water curing, and after 14 days, the permeability coefficient decreased to 10 -9 m / s.
[0106] 6. Maintenance-free ultra-thin seamless pavement
[0107] Fig.12 A comparison chart of maintenance-free ultra-thin seamless ECC pavement and traditional cracked concrete pavement. The ECC pavement has no transverse joints and is 100mm thick. After experiencing summer-winter cooling and shrinkage deformation, no cracks appeared. On the contrary, even if a transverse joint is set every 3.6 meters for the traditional concrete pavement and the pavement thickness is twice that of the ECC, multiple macro cracks still appear. The existence of cracks seriously affects the service life and driving comfort of the concrete pavement.
[0108] Fig.13 The results of the sensors embedded in the ECC pavement show that the ECC pavement was constructed in summer, with the initial pouring temperature of the material controlled at around 25°C, and then the maximum temperature rose to 34.5°C; the lowest temperature in winter was -8°C; the overall maximum temperature difference was 42.5°C, equivalent to a temperature deformation of 425με. Surprisingly, the ECC pavement did not have temperature cracks or volume shrinkage cracks.
[0109] Pavement deformation monitoring data show that the ECC pavement structure is always in a state of expansion and compression, that is, the intrinsic self-prestressed service, plus the intrinsic self-prestressed ECC material has the ability to self-heal cracks. Therefore, the ECC pavement in this example has achieved an innovative breakthrough in maintenance-free, ultra-thin and seamless. At the same time, it also has application inspiration for maintenance-free, ultra-thin and seamless ECC surface structures in the fields of bridge decks, airport runways, ultra-thin box culverts, ultra-thin large buoyancy floating bodies on the ocean, floor panels, concrete panels, pumped storage power station panels, anti-seepage panels, channel linings, tunnel linings, and renovation and repair of old structures.
[0110] 7. Ultra-thin box / floating body
[0111] The circular pipe unit is made of concrete of strength grade ECC and C40 in this example. The height of the pipe unit is 1m and the inner diameter is 300mm; the thickness of the ECC pipe is 50mm and the thickness of the C40 concrete pipe is 75mm. Fig.15 The force-displacement curves of ECC pipe and concrete pipe according to ASTM C407-19 trilateral compression test. The results show that even though the thickness of the ECC pipe unit is only 2 / 3 of that of the concrete pipe unit, its bearing capacity is increased by 20% and the ultimate displacement is increased by more than 300%.
[0112] On the basis of the improvement of bearing and deformation capacity, the failure mode of ECC pipe unit has also been fundamentally improved. Figure 16-Figure 17 As shown in the figure, the concrete pipe undergoes brittle failure after reaching the peak load, while the ECC pipe element exhibits a ductile failure mode with multiple cracks. Fig.16 The failure mode diagram shows that the cracks on the ECC pipe unit expand from the inner / outer edge along the pipe wall thickness direction, and then are captured in the ECC pipe wall and stop expanding. Therefore, the ECC pipe unit has the unique cracking advantage of "crack without penetration", and can achieve the technical breakthrough of "crack without leakage" during water service, which is particularly suitable for engineering applications such as water pipelines, ocean / canal floating bodies, etc.
[0113] ECC's corrosion resistance is much higher than that of concrete and steel, so it has the advantage of long service life in complex service environments such as the ocean. Figure 16-Figure 17 The circular tube unit shape in this example can also be used to make box-shaped floating bodies ( Fig.18 ), multi-layer composite structure ( Fig.19 ), and FRP and other reinforcement materials ( Fig. 20 ) and the box-type structure can also be combined with internal ribbed partitions. Due to its ultra-thin layer structure and high durability, it can play a unique advantage in light, high-strength, maintenance-free and high-buoyancy efficiency marine floating bodies.
Claims
1. An intrinsic self-prestressed ECC material, characterized in that: The intrinsic self-prestressed ECC material is composed of 50-150 parts of volume expansion components, 100-800 parts of cement, 400-1200 parts of supplementary cementitious materials, 400-800 parts of aggregates, 200-400 parts of water, 0-30 parts of water reducers, 0-50 parts of shrinkage reducers, 0-10 parts of thickeners, and 10-40 parts of fibers in terms of mass fraction.
2. The intrinsic self-prestressed ECC material according to claim 1, characterized in that: The mass fraction of the volume expansion component is 16%-32% of the total mass fraction of cement and the volume expansion component; the mass of the supplementary cementitious material is 0.8-3.6 times the total mass of cement and the volume expansion component.
3. The intrinsic self-prestressed ECC material according to claim 2, characterized in that: The intrinsic self-prestressed ECC material is composed of 75-150 parts of volume expansion components, 100-800 parts of cement, 400-1200 parts of supplementary cementitious materials, 400-800 parts of aggregates, 200-400 parts of water, 0-30 parts of water reducers, 0-50 parts of shrinkage reducers, 0-10 parts of thickeners, and 10-40 parts of fibers by mass fraction.
4. The intrinsic self-prestressed ECC material according to claim 3, characterized in that: The intrinsic self-prestressed ECC material is composed of 75-130 parts of volume expansion components, 100-800 parts of cement, 400-1200 parts of supplementary cementitious materials, 400-800 parts of aggregates, 200-400 parts of water, 0-30 parts of water reducers, 0-50 parts of shrinkage reducers, 0-10 parts of thickeners, and 10-40 parts of fibers by mass fraction.
5. The intrinsic self-prestressed ECC material according to claim 4, characterized in that: The intrinsic self-prestressed ECC material is composed of 100-130 parts of volume expansion components, 100-800 parts of cement, 400-1200 parts of supplementary cementitious materials, 400-800 parts of aggregates, 200-400 parts of water, 0-30 parts of water reducers, 0-50 parts of shrinkage reducers, 0-10 parts of thickeners, and 10-40 parts of fibers by mass fraction.
6. The intrinsic self-prestressed ECC material according to claim 5, characterized in that: The volume expansion component is an early volume expansion component or a combination of an early volume expansion component and a late volume expansion component.
7. The intrinsic self-prestressed ECC material according to claim 6, characterized in that: The early volume expansion component is one or more of sulphoaluminate cement, aluminate cement and calcium oxide; the late volume expansion component is one or a combination of magnesium oxide and steel slag.
8. The intrinsic self-prestressed ECC material according to claim 5, characterized in that: The supplementary cementitious material is one or more of fly ash, granulated blast furnace slag powder GGBFS, silica ash, volcanic ash, steel slag powder, and high-altitude land.
9. The intrinsic self-prestressed ECC material according to claim 5, characterized in that: The aggregate is one or more of machine-made sand, river sand, sea sand, desert sand, steel slag powder, tailings slag, limestone powder and rubber powder.
10. The intrinsic self-prestressed ECC material according to claim 5, characterized in that: The fiber is one or more of polypropylene PP fiber, polyethylene PE fiber, polyvinyl alcohol PVA fiber, steel fiber, basalt fiber, carbon fiber, glass fiber, and fly ash fiber.
11. A maintenance-free ultra-thin seamless ECC surface structure, characterized in that: The method is composed of the intrinsic self-stressed ECC material according to any one of claims 1 to 10, wherein the direct tensile deformation capacity of the intrinsic self-stressed ECC material is higher than 30,000 με, the width of the straight tensile crack is lower than 100 μm, and the permeability coefficient of the intrinsic self-stressed ECC material after being in contact with water for 14 days after experiencing a direct tensile deformation of no more than 20,000 με is lower than 10 -8 m / s; maintain 0.1MPa-10MPa intrinsic pre-compression stress under external constraints during service.
12. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 11, characterized in that: The maintenance-free ultra-thin seamless ECC surface layer structure maintains an intrinsic self-prestressed state throughout the service process and self-heals after cracks appear; the four-point bending flexural strength of the maintenance-free ultra-thin seamless ECC surface layer structure is 8MPa-30MPa, and the thickness of the maintenance-free ultra-thin seamless ECC surface layer structure is 0.5-30cm, which is 60% lower than the thickness of the concrete surface layer with the same compressive strength grade.
13. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 11 or 12, characterized in that: The preparation method of the maintenance-free ultra-thin seamless ECC surface layer structure is as follows: The volume deformation of the intrinsic self-prestressed ECC material during temperature and humidity curing is controlled to obtain a maintenance-free ultra-thin seamless ECC surface layer structure; the intrinsic self-prestressed ECC material maintains the intrinsic pre-compressive stress during service; the intrinsic self-prestressed ECC material is a high-ductility material.
14. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 13, characterized in that: The control of the volume deformation of the intrinsic self-prestressed ECC material during the temperature and humidity curing process is specifically: controlling the intrinsic self-prestressed ECC material to reach a maximum free expansion deformation between 1500με-10000με within 5 days during the temperature and humidity curing process, so that the free volume deformation after the later service stability is higher than 55% of the early maximum free expansion deformation.
15. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 14, characterized in that: The method of warm and wet curing includes water spraying curing and surface covering with plastic film, wet cloth, straw mat, moisturizing material and surface chemical moisturizing agent.
16. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 13, characterized in that: The temperature and humidity maintenance time is 0.25-3 days; the time after later service stability is 720 days or more.
17. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 16, characterized in that: The temperature and humidity curing process lasts for 0.5-2 days.
18. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 13, characterized in that: The temperature of the temperature and humidity curing is 10-40°C, and the humidity is greater than 95%.
19. The maintenance-free ultra-thin seamless ECC surface structure according to claim 12, characterized in that: Through any one or combination of secondary wet curing, adding steel slag, adding magnesium oxide, adding stone powder, the free volume deformation after later service stabilization is made higher than 55% of the early maximum free expansion deformation.
20. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 19, characterized in that: The secondary wet curing begins when the maximum expansion deformation shrinks to 60-80% of the maximum free expansion deformation, and the wet curing time is 0.25-3 days.
21. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 13, characterized in that: The temperature of the intrinsic self-prestressed ECC material is controlled at 5-30°C during mixing and transportation.
22. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 11 or 12, characterized in that: The construction method of the maintenance-free ultra-thin seamless ECC surface layer structure is that within 120 minutes from the start of construction, according to "GB / T2419-2020 "Determination Method for Fluidity of Cement Mortar", the fluidity of the intrinsic self-prestressed ECC material is between 120 mm and 220 mm.
23. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 22, characterized in that: The construction process is divided into one-time forming to achieve the designed thickness or into multiple layers of construction to achieve the overall designed thickness.
24. The maintenance-free ultra-thin seamless ECC surface layer structure according to claim 23, characterized in that: The construction method is one or more of injection molding, mold casting molding, 3D printing molding, rolling molding, self-compacting molding, and smearing molding.
25. An application of the maintenance-free ultra-thin seamless ECC surface structure according to claim 11 or 12, characterized in that: It is used for marine floating bodies, pavements, bridge decks, airport runways, ultra-thin box culverts, concrete panels, anti-seepage panels, pumped storage power station panels, floor panels, channel linings, tunnel linings, spray repair thin layers, and hand-applied repair layers.
Citation Information
Patent Citations
High-ductility cement-based material in ultralow-temperature environment as well as preparation method and application thereof
CN113087459A
Process method for repairing lining by adopting high-ductility cement-based composite material
CN116084993A
Self-stress desert sand ultrahigh-ductility concrete and preparation method thereof
CN116283168A
Crack control method for tunnel molded lining concrete
CN119266862A
Cited By
Anti-crack self-waterproof prestressed ECC with defect in-situ growth regulation and control function and preparation method of anti-crack self-waterproof prestressed ECC
CN122036300A
Defect in-situ growth regulation anti-cracking self-waterproofing prestressed ecc and preparation method thereof
CN122036300B
Low-fiber-content high-toughness self-prestressed concrete
CN122127116A